Special edition using Microsoft Office Outlook 2007 - DiGiacomo, Patricia (Que, 2006)
Every business professional faces challenges in managing their time to be as efficient and productive as possible. Information management has become an important everyday task in helping manage these challenges successfully, and Microsoft Outlook is the gold standard to help users stay organized. Outlook not only helps manage contacts, appointments, and tasks, it also serves as the e-mail and fax client. Outlook 2007 has been redesigned and improved with a new user interface, electronic business cards, RSS support, smart scheduling, anti-phishing capabilities, junk e-mail filter, and more. Case study sections called "Improving Your Outlook" illustrate how to apply the information learned in real-world situations. Troubleshooting sections in each chapter illustrate common problems that occur when using Outlook, followed by a detailed solution. With this book, you learn the latest features and improvements in Outlook by focusing on user productivity through real-world techniques in real-world environments. Introduction I Setting Up and Configuring Outlook 1 What's New in Outlook ... ... ... ... ... . 9 2 Getting Started and Getting Help ... ... ... . 25 3 Managing Outlook Folders ... 39 4 Creating Views and Print Styles ... ... ... ... 79 5 Customizing Command Bars . . 117 II Outlook as a Personal Information Manager 6 Managing Personal Information Using Outlook ... ... ... ... ... ... 139 7 Creating and Using Categories ... ... . 145 8 Customizing Outlook Today ... 161 9 Creating Contacts ... 179 10 Working with Contacts ... ... ... ... ... . 207 11 Address Books and Directory Services ... ... 247 12 Using the Outlook Calendar ... ... ... ... . 257 13 Collaborating with Calendars ... ... ... ... 301 14 Working with Tasks ... ... ... ... ... ... 321 15 Staying Organized with the Outlook Journal ... . 349 16 Using Outlook Notes ... ... ... ... ... . 367 III Outlook as a Mail Client 17 Working with Mail Accounts ... ... ... ... . 379 18 Creating New Messages ... ... ... ... ... 407 19 Receiving Messages ... ... ... ...